Inclusive education through the eyes of South African teachers. - Mbatha Stainbank, Yolanda (My University, 2018)
This study explored the attitudes of teachers in three types of South African schools (Mainstream, Full-service, and Special school) towards inclusive education in relation to the support that they are receiving in the implementation of inclusive education in their respective schools. Participants in this study were selected purposively from mainstream, full-service, and special schools within the Johannesburg South district. Data in the research was collected through individual teacher interviews. Data obtained was interpreted using qualitative methods. Participants were coded (in relation to the type of school they are from) in order to ensure anonymity in the results. Data was analyzed using Thematic Content Analysis. Thematic Content Analysis allowed the researcher to descriptively identify, analysis, and report themes. It involved the identifying of common themes throughout the text which describes significant aspects of the data in relation to the research question. The computer programme ATLAS was used in order to assist with the Thematic Analysis. Following the analysis of data, it was found that the attitudes of mainstream and full-service teachers towards inclusive education are mostly negative in comparison to that of teachers in special schools as a result of the discrepancies in the level of support each teacher receives to implement inclusive education (depending on the type of school they are in). The former has implications in terms of how effectively inclusive education is implemented in all schools in South Africa because in accordance to this study's findings support for teachers should not be based on only the type of school teachers are in but also the type of support teachers needs individually. Also, it was found that the ideals of inclusive education is not fully accepted by all stakeholders (more specifically the different units within the district) within the education department and this has influenced how teachers view the relevance of inclusive education policies. Considering the finding of the study, an exploration of how all stakeholders in the education system view and practice the policy of inclusive education is seemingly required in future research to better understand the state in which inclusive education is currently progressing in South Africa. Furthermore, due to teachers being major stakeholders in the implementation of inclusive education, it is important that continuous exploration of their attitudes and that which may influence their attitude towards inclusive education is done. Consequently, issues such as discrepancies in support towards teachers due to differences in types of school need to be further investigated.
A Dissertation submitted to the faculty of Humanities, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Masters of Educational Psychology in the Department of Psychology
Keywords: Education- South Africa; Teachers-- South Africa; Mainstream, Full-service, and Special school - South Africa